Progress in inorganic chemistry (Wiley & Sons, 2007)
Nowhere is creative scientific talent busier than in the world of inorganic chemistry experimentation. Progress in Inorganic Chemistry continues in its tradition of being the most respected avenue for exchanging innovative research. This series provides inorganic chemists and materials scientists with a forum for critical, authoritative evaluations of advances in every area of the discipline. With contributions from internationally renowned chemists, this latest volume offers an in-depth, far-ranging examination of the changing face of the field, providing a tantalizing glimpse of the emerging state of the science.